Historiography of ethnological study of Belarusians folk medicine of the 19th – the first half of the 20th century - Rabetz, Tatyana D. (Human in the Socio-Cultural Dimension, 2025)
The article carried out an objective and comprehensive analysis of the results and prospects of the study of folk medicine of Belarusians in the 19th – the first half of the 20th century. The main directions of development of scientific ideas on the problem in question are highlighted. The contribution of some ethnographers to the collection, systematisation and scientific understanding of into about on traditional means and methods of folk medicine was noted. It was concluded that it is necessary to clarify the essence of folk medicine as a significant element of Belarusian culture and to create a programme of systematic research of this cultural phenomenon.
Keywords: historiography; folk medicine of Belarusians; witchcraft; means of curing diseases; healing magic; incantations; medicinal plants; religious and mythological representations of Belarusians